PENGARUH IKLAN DAN WORD OF MOUTH (WOM) TERHADAP BRAND AWARENESS, SERTA IMPLIKASINYA PADA MINAT BELI PRODUK KOPI INSTAN GOOD DAY - niken dwita laraswati (Program Studi Ilmu Administrasi Bisnis, UPN Veteran Yogyakarta, 2018)
This study was conducted to determine the effect of Advertising and Word of Mouth (WOM) on Brand Awareness, and Its Implications on Interest in Buying Good Day Instant Coffee Products on consumers in Burjo Andeska Jl. Seturan Raya, Yogyakarta. The research uses explanatory type. The population in this study is infinite. The sample size in this study was 69 respondents. The sampling technique used was purposive sampling. Data analysis techniques using Descriptive Statistical Analysis and Inferential Statistical Analysis that uses the Path Analysis statistical method. The results of this study indicate that advertising has a significant effect on Brand Awareness, Word of Mouth (WOM) has a significant effect on Brand Awareness, Advertising has a significant effect on Purchase Interest, Word of Mouth (WOM) has a significant effect on Purchase Interest, There is a mediating effect on Advertising on Interest Buy through Brand Awareness, and there is a mediating effect of Word of Mouth (WOM) on Buy Interest through Brand Awareness. Key words: advertising, word of mouth (WOM), brand awareness, purchase intention